The Influence of Total Assets, Investment Breakdown, Inflation, and Interest Rates on Gross Premium Growth in the Indonesian General Insurance Industry (2018–2025) - Thony Warisman; Prayitno Basuki; Subhan Purwadinata (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the effect of Total Assets, Investment Details, Inflation, and Interest Rates on the Gross Premium of the general insurance industry in Indonesia for the 2018–2025 period. The research utilizes a quantitative approach with monthly secondary data obtained from the Financial Services Authority (OJK), the Central Bureau of Statistics (BPS), and Bank Indonesia (BI). The analysis technique used is multiple linear regression processed through EViews 12, consisting of classical assumption tests, partial test (t), simultaneous test (F), and coefficient of determination (Adjusted R²). The results show that Total Assets has a positive and significant effect on Gross Premium, Investment Details has a negative and significant effect on Gross Premium, Inflation has no significant effect on Gross Premium, while Interest Rates has a positive and significant effect on Gross Premium. Simultaneous testing indicates that all independent variables collectively have a significant effect on Gross Premium, explaining 47.60% of the model’s variance, while the remaining is influenced by other variables outside the model. The research findings suggest that the development of Gross Premium in Indonesia’s general insurance industry is highly driven by the internal financial strength of the firms rather than macro-level indicators individually, emphasizing that asset strengthening, prudent investment management, and corporate financial health are essential aspects of insurance industry growth